The interplay between hydrogen bonds and stacking/T-type interactions in molecular cocrystals - Aurora J. Cruz-Cabeza; Peter R. Spackman; Amy V. Hall (Communications Chemistry)
Abstract Supramolecular synthon and hydrogen bond pairing approaches have influenced the understanding of cocrystal formation for decades, but are hydrogen bonds really the dominant interaction in cocrystals? To investigate this, an extensive analysis of 1:1 two-component cocrystals in the Cambridge Structural Database was undertaken, revealing that stacking and T-type interactions are just as, if not more important than hydrogen bonds in molecular cocrystals. A total of 84% of the most common coformers in the dataset are aromatic. When analysing cocrystal dimers, only 20% consist of solely strong hydrogen bonds, with over 50% of contacts involving stacking and T-type interactions. Combining interaction strength and frequency, both hydrogen bond and stacking/T-type interactions contribute equally to the stabilisation of cocrystal lattices. Therefore, we state that crystal engineering and cocrystal design concepts of the future should not solely revolve around supramolecular synthon pairing via hydrogen bonds, but instead consider optimising both hydrogen bonding and stacking/T-type interactions.